Tracing Your Mississippi Ancestors - Webster, Anne L. (Anne Lipscomb) (Book collections on Project MUSE., 1994)
Where do you begin? In what resources will you find likely clues to guide you through the genealogical maze? For both novice and veteran researchers here is a guide that answers questions abut how to find your ancestors if they resided in Mississippi or dwelled there briefly during their migration. Included in this valuable handbook are more than six hundred descriptive profiles and printed sources - colonial, territorial, state, and local materials - that can help you follow the clues of your search.